Purchasing and supply management's identity: Crisis? What crisis?. Issue 1 (January 2020) - Ellram, Lisa M.; Harland, Christine M.; van Weele, Arjan; Essig, Michael; Johnsen, Thomas; Nassimbeni, Guido; Pagell, Mark; van Raaij, Erik; Rozemeijer, Frank; Tate, Wendy L.; Wynstra, Finn
Abstract: Purchasing and Supply Management (PSM) has been subjected to a number of examinations, all concluding that PSM is not an academic discipline as it lacks its own theories and common themes of research. It is perceived by many as an applied social science and field of research applying theories from other disciplines. But, to date, these examinations have not revealed more definitively what PSM is, i.e., its identity. This Notes and Debates paper was stimulated by two focused meetings, a question panel at IPSERA 2019 and solicited views from IPSERA participants. These were synthesized and developed through grounding them in identity and social identity theories. They are provided to stimulate the debate on PSM's internal and external identity coherence and legitimacy. Highlights: PSM has emerged as an important contributor to organizational success in conjunction with operations, marketing and logistics. Due to its multidisciplinary nature and frequent change in reporting relationships, PSM has not established a clear identity. PSM has not been a net contributor to development of theory. PSM theory development would support PSM as discipline, but not all are convinced that it is/should be a mono-discipline.